2021
DOI: 10.1051/e3sconf/202131701006
|View full text |Cite
|
Sign up to set email alerts
|

Thrifting Culture during the Covid-19 Pandemic and Its Impact on the Environment

Abstract: Buying and wearing second-hand clothes are still considered taboo and embarrassing by many people in Indonesia. However, a new phenomenon has emerged, namely the thrifting trend among young people during this pandemic. Thrifting means an activity of hunting used clothes. This study aims to 1) explain the cultural changes among young people related to thrifting; 2) knowing the motivation of thrifting among young people; 3) find a relationship between thrifting and the environment. The author uses cultural theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…A further study even identified six motivations for thrift shopping similar to those above, but adding hedonism as one of the reasons people thrift and explaining that someone can splurge by buying second-hand goods (Bardhi and Arnould 2005). Two studies carried out on a very micro scale (interviewing five people) on the practice of thrifting in Indonesia found similar findings, focusing on economic and environmental motivations (Lestari and Asmarani 2021;Ayu et al 2020). But these studies do not fully explain the rising popularity of thrifting in Indonesia.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…A further study even identified six motivations for thrift shopping similar to those above, but adding hedonism as one of the reasons people thrift and explaining that someone can splurge by buying second-hand goods (Bardhi and Arnould 2005). Two studies carried out on a very micro scale (interviewing five people) on the practice of thrifting in Indonesia found similar findings, focusing on economic and environmental motivations (Lestari and Asmarani 2021;Ayu et al 2020). But these studies do not fully explain the rising popularity of thrifting in Indonesia.…”
Section: Introductionmentioning
confidence: 80%
“…As one of the largest textile and garment producers in the world, Indonesia has also experienced a rapid increase in the business of trading second-hand fashion in the last few years (Machado et al 2019). Second-hand trading, popularly referred to as the practice of thrifting, has become especially common on social media platforms such as Facebook and Instagram, as well as e-commerce sites such as Shopee and Tokopedia (Utomo 2021;Lestari and Asmarani 2021). Most of the consumers of this kind of second-hand fashion are urban youth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the more stylish the SHC products, the more attractive the SHC is to the consumer. Today, most SHCs offer a current fashion style (Grimmer and Grimmer, 2022;Lestari and Asmarani, 2021), a unique or rare style (Ertz et al, 2017) and historical and cultural values (Perry and Chung, 2016). Accordingly, Generation Z feels that wearing such stylish SHC will improve their fashion presence (Hidayat et al, 2022).…”
Section: Generation Z Attitudes and Purchase Intentionmentioning
confidence: 99%
“…Fast fashion that has significant impacts to the environment [ Fig 1], synthetic materials and chemical produces low quality product for the sole purpose of accelerating mass production [2]. During the Pandemic many people reconsidering their consumption in purchasing fashion, its impact the income that has led many people seek more affordable price when it comes to fashion and become conscious about the environment [3], they do thrifting fashion to fulfil the styles and design for more anti-mainstream look. In order to maintain the waste generated by fashion industry, many ways to achieve cleaner activities, such as conserving natural resources, recycling the materials, more durable materials or repairable, maximizing value through any strategies for more sustainable and circular approaches.…”
Section: Introductionmentioning
confidence: 99%